Penerapan Model Problem Based Learning Berbantuan Flashcard untuk Meningkatkan Aktivitas dan Hasil Belajar Peserta Didik Kelas XI SMA DEK Padang - Sinaga, Ance Delprina; Ardi, Ardi; Fitria, Kartika (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the improvement of activities and learning outcomes of students in class XI Phase F SMA DEK Padang with the application of the PBL model assisted by flash card media on respiratory system materials. This research is a Classroom Action Research (CAR) with a pre-experimental method. The population in this study is students at SMA DEK Padang. The instruments used are interview sheets, test questions, and non-tests. The data produced is in the form of quantitative data and analyzed based on the average score and completeness of student learning, attitude values and skill values measured by tests and non-tests. The results of the study show that the application of the PBL model assisted by flashcard media has proven to be effective in improving students' activities and learning outcomes. Learning activities increased from 72% in the first cycle to 83.25% in the second cycle. Meanwhile, cognitive learning outcomes that had declined in cycle I showed a significant increase in cycle II, reaching 72% learning completion. Thus, the flashcard-assisted PBL model can be used as an alternative learning model that is able to increase student engagement and learning outcomes, especially for those who have a visual learning style.